Jan Václav, Count Michna of Vacínov and Emblematic Decoration of the St. James' Church in Kratonohy (Theatrum historiae, 2007)
The paper focuses on the building history, ceiling decoration and furnishings of the St. James' Church in Kratonohy (East Bohemia). The originally gothic object was markedly rebuilt within the years 1710-1711 in baroque style. The building transformation and a new interior decoration were iniciated by Jan Václav, Count Michna of Vacínov to whom the landed estate of Kratonohy belonged in the years 1701-1716. The baroque vaults were covered by the stucco net of painted emblems of devotional themes. The fifteen scenes apparently derived its models from the treatise Amoris divini et humani antipathia that were first published in 1628 in Paris in the bilingual English-French version and several times reedited during the 17th Century. The editor Michel van Lochom (Lochem) freely utilized the elder emblematic production of the Dutch provenance. Other three emblematic scenes placed on the triumphal arch of the Kratonohy church stem from the enigmatic graphic illustrations of contemporary popular work by Spanish diplomatist Diego de Saavedra Fajardo (1584-1648). All the used emblems are associated with the idea of imitatio Christi. The decoration programme in Kratonohy doesn´t link to any of the elder Bohemian emblematic cycles and thus it is an iconographic curiosity here. The furnishing of the Kratonohy church had been executed in unusual forms, too. The pulpit in the form of the sea monster belongs to the group of so called Naturkanzeln imitating nature and it is probably the first known example of this topic in Central Europe. The architecture of the main altar was inspired by the image of the sepulchre of St. James the Great in Santiago de Compostela, being performed as the cave decorated by the shells and imitations of the gemstones.